A prospective multi‐faceted interventional study of blood bank technologist screening of red blood cell transfusion orders: The START study. Issue 2 (10th January 2021) - Kron, Amie T.; Collins, Allison; Cserti‐Gazdewich, Christine; Pendergrast, Jacob; Webert, Kathryn; Lieberman, Lani; Zeller, Michelle P.; Harding, Sheila R.; Nahirniak, Susan; Prokopchuk‐Gauk, Oksana; Lin, Yulia; Mendez, Brent; et al.
Abstract: Background: Transfusion of red blood cells (RBC) is a common procedure, which when prescribed inappropriately can result in adverse patient outcomes. This study sought to determine the impact of a multi‐faceted intervention on unnecessary RBC transfusions at hospitals with a baseline appropriateness below 90%. Study Design and Methods: A prospective medical chart audit of RBC transfusions was conducted across 15 hospitals. For each site, 10 RBCs per month transfused to inpatients were audited for a 5‐month pre‐ and 10‐month post‐intervention period, with each transfusion adjudicated for appropriateness based on pre‐set criteria. Hospitals with appropriateness rates below 90% underwent a 3‐month intervention which included: adoption of standardized RBC guidelines, staff education, and prospective transfusion order screening by blood bank technologists. Proportions of RBC transfusions adjudicated as appropriate and the total number of RBC units transfused per month in the pre‐ and post‐intervention period were examined. Results: Over the 15‐month audit period, at the 13 hospital sites with a baseline appropriateness below 90%, 1950 patients were audited of which 81.2% were adjudicated as appropriate. Proportions of appropriateness and single‐unit orders increased from 73.5% to 85% and 46.2% to 68.2%, respectively from pre‐ to post‐intervention ( P  < .0001). Pre‐ and post‐transfusion hemoglobin levels and the total number of RBCs transfused decreased from baseline ( P < .05). The median pre‐transfusion hemoglobin decreased from a baseline of 72.0 g/L to 69.0 g/L in the post‐intervention period ( P  < .0001). RBC transfusions per acute inpatient days decreased significantly in intervention hospitals, but not in control hospitals ( P  < .001). The intervention had no impact on patient length of stay, need for intensive care support, or in‐hospital mortality. Conclusion: This multifaceted intervention demonstrated a marked improvement in RBC transfusion appropriateness and reduced overall RBC utilization without impacts on patient safety.